Social work : a critical approach to practice - Fook, Jan (London : SAGE, 2016)
In this text, Jan Fook provides a textbook that is organised with a reflective approach to social work. The reader is encouraged to develop his or her own ideas, using the material covered in this book.
pt. 1. Critical Potential and Current Challenges -- Ch. 1. The Critical Tradition of Social Work -- Ch. 2. Current Contexts of Practice: Challenges and Possibilities -- pt. 2. Rethinking Ideas -- Ch. 3. New Ways of Knowing -- Ch. 4. Power -- Ch. 5. Discourse, Language and Narrative -- Ch. 6. Identity and Difference -- pt. 3. Redeveloping Practices -- Ch. 7. Critical Deconstruction and Reconstruction -- Ch. 8. Empowerment -- Ch. 9. Problem Conceptualisation and Assessment -- Ch. 10. Narrative Strategies -- Ch. 11. Contextual Practices: Strategies for Working in and with Contexts -- Ch. 12. Ongoing Learning.
Previous edition: 2012.
Includes bibliographical references (pages 215-224) and index.
Keywords: Socialt arbete; Social service; Social service; Social service; Social work